Deoxypyrimidine monophosphate bypass therapy for thymidine kinase 2 deficiency. Issue 8 (26th June 2014) - Garone, Caterina; Garcia‐Diaz, Beatriz; Emmanuele, Valentina; Lopez, Luis C; Tadesse, Saba; Akman, Hasan O; Tanji, Kurenai; Quinzii, Catarina M; Hirano, Michio
Abstract Autosomal recessive mutations in the thymidine kinase 2 gene (TK2) cause mitochondrial DNA depletion, multiple deletions, or both due to loss of TK2 enzyme activity and ensuing unbalanced deoxynucleotide triphosphate (dNTP) pools. To bypass Tk2 deficiency, we administered deoxycytidine and deoxythymidine monophosphates (dCMP+dTMP) to the Tk2 H126N (Tk2−/−) knock‐in mouse model from postnatal day 4, when mutant mice are phenotypically normal, but biochemically affected. Assessment of 13‐day‐old Tk2−/− mice treated with dCMP+dTMP 200 mg/kg/day each (Tk2−/−200dCMP/dTMP) demonstrated that in mutant animals, the compounds raise dTTP concentrations, increase levels of mtDNA, ameliorate defects of mitochondrial respiratory chain enzymes, and significantly prolong their lifespan (34 days with treatment versus 13 days untreated). A second trial of dCMP+dTMP each at 400 mg/kg/day showed even greater phenotypic and biochemical improvements. In conclusion, dCMP/dTMP supplementation is the first effective pharmacologic treatment for Tk2 deficiency.